Predator-associated vocalizations in North American red squirrels (Tamiasciurus hudsonicus): are alarm calls predator-specific? - Digweed, Shannon; Rendall, Drew (My University, 2009)
North American red squirrels are a small-bodied, solitary, territorial species that faces a diversity of predators. One report suggested that red squirrels produce two distinct vocalizations to aerial and ground predators: a tonal ‘seet’ and a broadband ‘bark’, respectively. This categorical mapping between alarm call variants and predator classes suggested that red squirrels might manifest a system of predator- specific, referential alarm calls. To test this hypothesis, we undertook a multi-year study of red squirrels in southern Alberta, Canada. We report details of alarm call production by red squirrels during natural predator encounters, in response to a series of predator simulation experiments, and during encounters with non-predatory species, including conspecific territorial intruders. The pattern of alarm call production was consistent across these conditions and involved two main call types, the tonal seet call and a more broadband ‘seet-bark’ call, that corresponded closely to the bark call identified previously. However, there was little evidence that call production was specific to particular predator classes. Instead, the two call types were produced together in mixed bouts to predators of all types as well as to non-predatory species and conspecific intruders. These outcomes contradict the hypothesis that alarm calls in red squirrels are referentially-specific. We suggest instead that calls might be directed primarily at the intruders themselves and function to announce their detection and possibly aid in deterring or repelling them. This possibility is consistent with a variety of other important features of the behavior and life history of red squirrels.
Keywords: communication; alarm calls; red squirrels